The Steel Framed Dome - Stevens, David E.; Odom, Gerald S. (Engineering Journal, 1964)
Many engineers when first confronted with the design of a steel framed dome are dismayed by the complexity of these often highly indeterminate, three dimensional space frames. Furthermore, on locating references in the literature, many are further confused to find that there is no unanimity of opinion among the various investigators as to proper methods of analysis and design. Despite the fact that domes are one of the oldest structural forms in existence and that recent years have seen a revival of this form and a growth of its popularity, few scientific investigations have been made. Opinions vary widely from those who advocate rigorous methods of analysis based on deformations or simultaneous displacements to those who advocate analysis by simple statics.Many steel framed domes have been designed and built in recent years. However, despite the increasing popularity of this type of structure, little new design information has beenpublished. For this reason, engineers who wish to investigate the steel framed dome for the first time can find little guidance based on the practical experience of others. The purpose of this paper is to provide a practical discussion of the analysis and design of the Schwedler dome,one of the more popular types of steel framed domes. Included are a design example and a list of references. The opinions expressed herein are those of the authors, based on both field and office experience over the past fifteen years and upon a study and evaluation of those publications listed in the bibliography at the end of this paper.